2019
DOI: 10.1371/journal.pone.0222084
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses to affiliation during conversation: Comparing neurotypical males and males with Asperger syndrome

Abstract: We examined the emotional and psychophysiological underpinnings of social interaction in the context of autism spectrum disorder, more specifically, involving participants diagnosed with Asperger syndrome (AS). We recorded participants’ autonomic nervous system (ANS) activation (electrodermal activity, heart rate, and heart rate variability) and facial muscle activation during conversations in two different types of male dyads: (1) ten dyads where one participant has been diagnosed with AS (AS/NT dyads) and (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…For example, studies adopting these approaches directly investigate emotions in interactive contexts (Nummenmaa et al, 2012) both in neurotypical populations and other populations, e.g. individuals with an autism spectrum condition (Stevanovic et al, 2019). Because abstract concepts are more variable across contexts compared to concrete concepts, and because they are more strongly influenced by the social dimension, it is high time to take inspiration from other domains in order to start employing novel, interactive methods to investigate their use (Falandays & Spivey, 2019).…”
Section: Language and The Flexibility Of Grounded Cognitionmentioning
confidence: 99%
“…For example, studies adopting these approaches directly investigate emotions in interactive contexts (Nummenmaa et al, 2012) both in neurotypical populations and other populations, e.g. individuals with an autism spectrum condition (Stevanovic et al, 2019). Because abstract concepts are more variable across contexts compared to concrete concepts, and because they are more strongly influenced by the social dimension, it is high time to take inspiration from other domains in order to start employing novel, interactive methods to investigate their use (Falandays & Spivey, 2019).…”
Section: Language and The Flexibility Of Grounded Cognitionmentioning
confidence: 99%
“…Indeed, different research groups have been focussing on the relationship between language use and physiological processes (see, e.g. Hardacre, 2020; Stevanovic et al., 2017, 2019, 2021), and even combining different techniques (e.g. eye tracking and electroencephalography (EEG): Hollenstein et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to describing the details of how various lexical, prosodic, and facial expression of emotion are embedded in, and regulated by, the sequential structures of social interaction, there have been attempts to consider the psychophysiological underpinnings of social interactional phenomena in a level of detail that has been unprecedented in the past [ 2 , 3 ]. This line of research has also opened a fresh avenue to also consider those asymmetries of interactions that may be attributed to participants’ specific clinical and neurological conditions, such as autism spectrum disorder [ 4 ]. This paper presents a contribution to this emerging line of research.…”
Section: Introductionmentioning
confidence: 99%
“…First, a set of studies has focused on how events of social interaction relate to an increase or decrease in the indicators of participants’ emotional arousal [ 2 , 3 , 12 14 ]. For example, focusing on storytelling and story reception, Peräkylä and colleagues [ 3 ] found that an increased level of affiliative story reception is associated with a decrease in the storyteller’s arousal and an increase in the story recipient’s arousal, as indicated in the participants’ SC response during the storytelling episodes (see also [ 4 ]). Second, there are studies on the momentary similarity (e.g., synchronicity or correlation) in the physiological changes in the participants interacting with each other [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%